Role of biochemistry, cytology, and biopsy in the etiological diagnosis of pleural effusion- a clinical study - Bedi, Manan; Joshi, Nalin (International Journal of Medical Research and Review, 2020)
Introduction:Pleural effusion is the most common pleural disorder. It refers to excessive or abnormal accumulation of fluid in the pleural space. It is a commonly occurring medical problem caused by various pathological conditions. To treat patients appropriately, it is important to establish an accurate etiological diagnosis. Material and Method: This is an observational study conducted at a tertiary health care center. The pleural effusion was assessed clinically, biochemically, bacteriologically, cytologically, and histopathologically. Result: Tuberculosis was the most common etiology, followed by malignancy. A pleural biopsy was done in 70 patients. Pleural tissue was obtained in 65 cases. On histopathology,Malignancy was diagnosed in 15, tuberculosis in 35, and non-specific inflammation in 13 cases. Out of 35 histological proven tuberculosis cases, 26 cases had adenosine de-aminase (ADA) more than 70 u/l. Conclusion:Every pleural effusion is not due to tuberculosis but can be due to other causes, malignancy should always be excluded. Pleural fluid cytology and biopsy can give a definite diagnosis in a significant number of cases of pleural effusion. Tuberculosis is still the most common cause of pleural effusion followed by malignancy.